Pathogenetic Mechanisms And Clinical Manifestations Of Cardiac Inficiency With Normal Systolic Function Of The Left Ventricle (Analytical Review) - Kurbanova Shohista Tojiddin qizi (International Journal of Medical Sciences And Clinical Research, 2025)
Left ventricular diastolic dysfunction remains the central link in HFpEF pathogenesis, including slowed active myocardial relaxation and decreased heart chamber flexibility. The molecular mechanisms of diastolic dysfunction include cardiomyocyte calcium homeostasis disorders, changes in titin properties, fibrous changes in the myocardium, and energy metabolism disorders. These processes lead to an increase in left ventricular filling pressure and the development of clinical manifestations of congestive heart failure while maintaining normal myocardial contractility.